Images from the wards : diagnosis and treatment - Studdiford, James S. (Saunders/Elsevier, 2010)
A visual resource for in-training and practicing physicians that presents a review for diagnosis and treatment with images - selected from a large bank of medical pictures in a teaching database at Jefferson Medical College - that underscore important teaching points.